PENGARUH GETARAN TERHADAP MUTU BETON PADA KONDISI FASE PLASTIS SAMPAI FASE SETTING - Asril, Syamsul; Wiyono, Sugeng; Elizar, Elizar (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2023)
Vibration caused by vehicles crossing the side of the road which is in the process of casting and compacting the rigid road pavement layer needs to be considered, especially during the plastic phase and setting phase. These two phases are estimated to greatly affect the quality of the concrete which will have an impact on damage to the concrete. The purpose of this study was to determine the effect of vibration on the quality of concrete in the plastic phase and setting phase. The research method uses a vibration modification machine simulation by placing concrete test objects according to the age of the concrete in the plastic phase and the setting phase. The magnitude of the vibration frequency of the vibrated vehicle is 3 Hertz. The vibration value used is in accordance with the field conditions of the vehicle plunging the road that is being repaired/constructed in an area that is traversed by heavy traffic and large loads, namely the Gajah Mada Duri Road area. The results showed that the effect of vibration on the condition of the plastic phase of the vibrated concrete will still meet the quality of concrete with an average value of Fs 51.99 Kg/cm2 Fs 45. While the Setting phase does not meet the quality of concrete with an average value of Fs 42, 78 Kg/cm2 Fs 45. This means that vibration due to passing vehicles will have the quality of the concrete during the setting phase.